Now more than ever, this planet needs truly inclusive community development efforts that tolerate, embrace – even celebrate – difference*. Issue 1 (1st January 2016) - Lamie, David
Abstract: Community development scholars and practitioners need to direct more attention to diversity to address the challenges of our past, present, and future. The Community Development Society's Principles of Good Practice should be used as a framework, but this approach needs to be continuously reviewed and reinvigorated. This essay was prepared as the Presidential Address for the 2015 conference of the Community Development Society held in Lexington, Kentucky.